Autophagy: Multiple Mechanisms to Protect Skin from Ultraviolet Radiation-Driven Photoaging. (13th December 2019) - Wang, Mei; Charareh, Pourzand; Lei, Xia; Zhong, Julia Li
Abstract : Autophagy is an essential cellular process that maintains balanced cell life. Restriction in autophagy may induce degenerative changes in humans. Natural or pathological aging of susceptible tissues has been linked with reduced autophagic activity. Skin photoaging is an example of such pathological condition caused by ambient solar UV radiation exposure. The UV-induced production of reaction oxygen species (ROS) has been linked to the promotion and progression of the photoaging process in exposed tissues. Accordingly, it has been suggested that autophagy is capable of delaying the skin photoaging process caused by solar ultraviolet (UV), although the underlying mechanism is still under debate. This review highlights several plausible mechanisms by which UV-induced ROS activates the cellular signaling pathways and modulates the autophagy. More specifically, the UV-mediated regulation of autophagy and age-related transcription factors is discussed to pinpoint the contribution of autophagy to antiphotoaging effects in the skin. The outcome of this review will provide insights into design intervention strategies for delaying the phenomenon of sunlight-induced photodamage, photoaging, and other aging-related chronic diseases based on factors that activate the autophagy process in the skin.